A pooled RT-PCR testing strategy for more efficient Covid-19 pandemic management - Ayaz, Akif; Öztürk Demir, Aslı Güner; Öztürk, Gürkan; Koçak, Mehmet (Elsevier, 2022)
Objectives: RT-PCR testing is indispensable in Covid-19 pandemic management. With the spread of the pandemic with emerging variants, the RT-PCR capacity is overburdened and new strategies and capabilities need to be established. One option is the pooled RT-PCR testing. Design: We conducted an experiment with various mixtures of Covid-19 samples known to be negative and positive, and investigated the impact of pool size and mixture level on final cycle threshold (CT)- measures. More specifically, 5, 10, and 20 Covid-19 negative samples are combined with 1, 2 or 3 low-CT or high-CT Covid-19 positive samples. Results: We have shown that average input CT and number of high and low CT samples in the pool are the main drivers of the final CT assessment, making the detectability easier. Pool size was not significantly associated with Final CT albeit suggestive. Conclusions: We conclude that pooled RT-PCR testing strategy does not reduce the sensitivity of RT-PCR and thus provides a practical way to expand the RT-PCR screening capacity in pandemic management. The pool size not being significnat, we recommend that the pool size of 20 would be a practical level reducing the time to obtain the results and the cost of RT-PCR testing needs.
Keywords: Covid-19 Testing; Cycle Threshold; Pandemic Management; Pooled RT-PCR; Virus Screening